(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Today, many measures are being taken to improve the quality of education in our country. In particular, the practical work carried out in the buildings of the general education school finds its expression. This article talks about the shortcomings, problems and achievements of the interiors of general education school buildings in the years of Soviet colonialism and independence in Uzbekistan.